(untitled) (Research, Society and Development, 2021)
Introduction: Brazilian law defines rape as the most serious type of sexual abuse. Rape consists of any act performed, for sexual purposes without the consent of one of the parties involved, violating the right of the other. Objectives: To identify the role of the nurse in the assistance provided to the rape victim and to analyze the nursing assistance in relation to the rape victims. Methodology: This is a study with a qualitative approach, of the integrative review type, which had as a database the Virtual Health Library Nursing using the Health Sciences Descriptors (DeCS Nursing; Rape; Nursing assistance. Articles were selected complete, in Portuguese and English, published between 2011 and 2021. At the end of the application of the criteria, 6 articles emerged for thorough reading and construction of the content. Results and discussion: Two categories were developed for data analysis Category I - Socio-cultural aspects of rape; Category II -The nursing professional facing the victims of rape. Final considerations: It is concluded that the nurse is a leading professional in assisting the rape victim and that it is necessary to constantly carry out training to improve care.